Dry biorefining maximizes the potentials of simultaneous saccharification and co‐fermentation for cellulosic ethanol production. Issue 1 (6th October 2017) - Liu, Gang; Zhang, Qiang; Li, Hongxing; Qureshi, Abdul S.; Zhang, Jian; Bao, Xiaoming; Bao, Jie
Abstract: Despite the well‐recognized merits of simultaneous saccharification and co‐fermentation (SSCF) on relieving sugar product inhibition on cellulase activity, a practical concomitance difficulty of xylose with inhibitors in the pretreated lignocellulose feedstock prohibits the essential application of SSCF for cellulosic ethanol fermentation. To maximize the SSCF potentials for cellulosic ethanol production, a dry biorefining approach was proposed starting from dry acid pretreatment, disk milling, and biodetoxification of lignocellulose feedstock. The successful SSCF of the inhibitor free and xylose conserved lignocellulose feedstock after dry biorefining reached a record high ethanol titer at moderate cellulase usage and minimum wastewater generation. For wheat straw, 101.4 g/L of ethanol (equivalent to 12.8% in volumetric percentage) was produced with the overall yield of 74.8% from cellulose and xylose, in which the xylose conversion was 73.9%, at the moderate cellulase usage of 15 mg protein per gram cellulose. For corn stover, 85.1 g/L of ethanol (equivalent to 10.8% in volumetric percentage) is produced with the overall conversion of 84.7% from cellulose and xylose, in which the xylose conversion was 87.7%, at the minimum cellulase usage of 10 mg protein per gram cellulose. Most significantly, the SSCF operation achieved the high conversion efficiency by generating the minimum amount of wastewater. Both the fermentation efficiency and the wastewater generation in the current dry biorefining for cellulosic ethanol production are very close to that of corn ethanol production, indicating that the technical gap between cellulosic ethanol and corn ethanol has been gradually filled by the advancing biorefining technology. Abstract : Dry acid pretreatment and biodetoxification (DryPB) maximized the commercialization potentials of cellulosic ethanol by elevating the ethanol titer (11‐13%, v/v) to corn ethanol level and minimizing the cellulase usage to 10‐15 mg per gram of proteins. The wastewater generation was reduced to zero starting from dry acid pretreatment, biodetoxification, to simultaneous saccharification and co‐fermentation (SSCF). The results indicate that the technical gap between cellulosic ethanol and corn ethanol has been filled by advancing biorefinery technology.